All you can eat: greed, lust, and the new capitalism - McQuaig, Linda (Penguin, 2001)
Explains the mired history of social and economic thinking that has culminated in the new capitalism. McQuaig argues that instead of shaping our society to fit the economy, we must shape the economy to fit the society we want. 2001.
Economics
Keywords: business & economics; capitalism; capitalism - history; economic history; free enterprise; political science

Reply to Professor Levine on Rhetoric and Reality in American Welfare History - Kern, William S. (Journal of Economic Issues (Association for Evolutionary Economics), 2001)
The article replies to professor David Levine's rhetoric and reality in American welfare history. The author largely agrees with Professor Levine's conclusion that the impact of the application of the principles of 1834 on contemporary welfare reform is "far more potent rhetorically than it is in fact" (733) and that "the slowly expanding mild welfare state is here to stay" (741). Levine argues that this is the result of the emergence and persistence of a "New Deal consensus" regarding the responsibility of government to secure macroeconomic stability and individual security that survives from its origin in the 1930s till today. The questions that arise are why this consensus emerged when it did and why it persists. In his paper the author attempts to explain why the reemergence of the rhetoric and practice of welfare reform had occurred, and he argues that an answer could be found in ideas developed by Karl Polanyi in The Great Transformation (1944). It had been argued that the logic of the self-regulating market required the denial of a right to life outside the market. This was affirmed in the passage of the New Poor Law and in the rhetoric and practices of current welfare reform. However, Polanyi's Great Transformation also provided us with an explanation of the factors which underlie the emergence of the New Deal consensus in the 1930s, the persistence of the welfare state, and the largely rhetorical impact of the principles of 1834 on current welfare reforms.
Economics
Keywords: United States; economic conditions - United States; economic history; macroeconomics; public welfare; reforms; welfare economics

Chapter 6: Our time - Heiskala, Risto (Will Europe Work?, 2001)
The article focuses on Europe in the age of global networks and flowing identities. In the article the author discusses the articulation of Europe. He starts with a discussion on the identity of Europe, goes on with a discussion of globalization and closes with an attempt to tie these two themes together. He then raises, in a new context, sociologist Karl Polanyi's question: "What Kind of a Time Is Our Time?" Throughout the article, specific emphasis is put on the European Union, as this network state currently uniting fifteen and in the nearest future possibly twice as many European states as today is often what is referred to combined with the term "Europe", even if it would be a mistake to believe that these two are identical. The article also throws light on the affect of Islam on the countries of Europe. In several European countries there are enclaves of millions of Muslim migrant workers and there are Muslim countries at the borders of Europe in North Africa and the Middle East.
Sociology
Keywords: Europe; Islam; globalization; identity (philosophical concept); immigrants

A Karl Polanyi Revival - Mendell, Marjorie (Canadian Dimension, 2001)
Presents insights from the book 'The Great Transformation,' by Karl Polanyi. Concerns that the economic benefits of globalization override political and social costs; Polanyi's vision of democratic socialism not coordinated by central planners; Research into the origins of economic institutions.
N/A
Keywords: Great Transformation; The (Book); economics - research

Planning and the Politics of Markets: Some Lessons from Financial Regulation in Nepal - Rankin, Katharine N. (International Planning Studies, 2001)
This paper calls for an explicit return to questions about the normative foundations of planning theory and practice. It argues that a simultaneous reading of Karl Polanyi with Friedrich von Hayek can contribute to developing an ethical basis for tempering market rationality with social rationality in the current global economic conjuncture. Empirically, the paper investigates recent initiatives in Nepal to provide social protections (à la Polanyi) through financial market rules. In the face of threats to the progressive legacy in planning practice posed by the prevailing neoliberal orthodoxy, Nepal's targeted lending policies and microcredit programmes offer some optimism about the potential to embed welfare provisions within market regulation, especially when compared to developments in other countries. At the same time, however, the perspectives of rural women explored here through critical ethnography raise key questions about the capacity of these regulations to generate social opportunity and highlight a role for locally situated social criticism in progressive planning practice.
Geography
Keywords: HAYEK; Friedrich A. von (Friedrich August); 1899-1992; Nepal; financial regulation; international planning studies; markets; planning; social protection

Discourses on peace and development - Hettne, B. (Progress in Development Studies, 2001)
Assuming a close relationship between peace and development, this paper analyses a succession of schools of thought in development forming part of three distinct, historically contextualized development and security discourses: the industrialization imperative in the emerging state-system in nineteenth-century Europe, the international concern with global poverty in the bipolar post second world war world and the current meaning of development in a globalized and increasingly chaotic world. The third of these discourses contains major challenges for development theory. The discourses are related to great transformations in political economy, understood in Polanyian terms as tensions between market expansion and societal response.
Peace Studies; Development Studies
Keywords: conflict; development theory; discourse; economic development; market expansion; peace; peace - economic aspects; security

Constructing a European Market: Standards, Regulation, and Governance - Egan, Michelle P. (Oxford University Press, 2001)
'An excellent contribution to our understanding of the political construction of markets... This is a well-written book, enjoyable to read as well as being very informative. I view this volume as a 'must read' for all scholars and graduate students in the areas of government and business, the politics of market economies and comparative politics in general. Michelle Egan's description and explanation of market construction and its impact on business standards, regulation and governance will be valuable to all of us for many, many years to come.' -Henry Jacek, McMaster University; Polibus: Newsletter of the IPSA Research CommitteeThis book provides a detailed analysis of the policies and institutions used by the EU to create a single market. Through a historical overview, sectoral case studies, and an assessment of recent policy initiatives, the author provides a comprehensive account of the evolution of European economic integration.
Political Science; Economics
Keywords: European Court of Justice; European Union; United States; business & economics; economic policy; harmonization; market integration; mutual recognition; public policy; regulation; single market; standards; trade barriers

Karl Polanyi and the creation of the "market society" - Gootenberg, Paul (The other mirror : grand theory through the lens of Latin America (Edited by Centeno, Miguel Angel, López-Alves, Fernando)., 2001)
History
Keywords: Latin America; economic history; philosophy; politics and government; social sceinces

Karl Polanyi's Great Transformation and the Current Transformations in Central Europe - Hake, Eric R.; Neale, Walter C. (Economic transition in historical perspective: Lessons from the history of economics, 2001)
Economics
Keywords: agriculture; collectives; communes; comparison of public and private enterprises and nonprofit institutions; contracting out; economic thought; history of economic thought: individuals; illegal behavior; legal institutions; nonprofit institutions; privatization; public enterprises; socialist systems and transitional economies: legal institutions; transitional economies

Institutional Investors and Polanyi's Double Movement: A Model of Contemporary Currency Crises - Harmes, Adam (Review of International Political Economy, 2001)
This article constructs a model of contemporary currency crises which incorporates the role played by institutional investors and the dynamics associated with Karl Polanyi's notion of the "double movement." Polanyi's double movement, and its recognition of the need to integrate politics with economics, is used to explain why so many governments are prone to pursue policies that lead to a speculative attack against fixed exchange rates and why virtually every modern fixed exchange rate regime has ended in crisis. Evidence on the short-term and herd behaviour of institutional investors is used to explain why contemporary currency crises do not appear to be justified by underlying economic fundamentals and why these crises do so much more damage than their earlier counterparts. The model is then applied to the 1992 European Exchange Rate Mechanism crisis, the 1994 Mexican peso crisis and the 1997 East Asian crisis. While recognizing that variations exist in the specific circumstances of each episode, the argument of this article is that the progression of events do seem to conform to the model presented.
Political Science
Keywords: corporate finance and governance; double movement; economic development; financial instruments; financial markets; foreign exchange; institutional investors; international linkages to development; international monetary arrangements and institutions; international political economy; non-bank financial institutions; pension funds; role of international organizations; saving and capital investment

Contesting the "Great transformation" : local struggles with the market in South India - Herring, Ronald (Agrarian studies : synthetic work at the cutting edge, ed. by James C. Scott and Nina Bhatt, 2001)
Political Science; Development Studies
Keywords: India; agrarian studies

Regulationist and Autopoieticist Reflections on Polanyi's Account of Market Economies and the Market Society - Jessop, Bob (New Political Economy, 2001)
This article re-interprets and develops Polanyi’s substantive institutionalist analysis of capitalist market economies and the market society in the light of two more recent approaches to the same issues. These are the Parisian ‘regulation school’ on contemporary capitalism and systems-theoretica l accounts of the modern economy. All three regard the capitalist economy (or, for autopoietic systems theory, the market economy) as an operationally autonomous system that is nonetheless socially embedded and needful of complex forms of social regulation. For each, an adequate account of economic activities should explore how they are related to the wider social environment; how they are embedded in a wider nexus of social institutions; how the latter assist in reproducing the capitalist (or market) economy; and how their development is coupled to that of these and other environing institutions. There are also some important differ- ences among these approaches, however, which enable an exploration of their respective limitations and also provide useful bases for further theoretical and empirical research. Thus, after presenting these three perspectives on the institutedness and embeddedness of economies. I consider some basic problems in analysing the improbable stability and reproducibility of the capitalist economy, paying particular attention to governance and meta-governance.
Sociology; Political Science
Keywords: capitalism; economics; market society; political economy; regulation school; substantive approach

Groundwork for an Institutional Economic Approach to 'Transition': Smith and Polanyi Reconsidered - Ozveren, Eyup (Economic transition in historical perspective: Lessons from the history of economics, 2001)
Economics
Keywords: Marxist; SMITH; Adam; 1723-1790; current heterodox approaches: institutional; evolutionary; history of economic thought; history of economic thought through 1925: socialist; history of economic thought: classical; history of economic thought: individuals; socialist systems and transitional economies: performance and prospects P27

What Karl Polanyi Found in Dahomey - Sandall, Roger (The culture cult : designer tribalism and other essays, 2001)
A study of the social effects of romantic primitivism.
Anthropology
Keywords: alternative lifestyles; culture; meningen; modern civilization - public opinion; primitive societies - public opinion; primitivism